Vehicle Security System using Short Message Service (SMS) as a Danger Warning in Motorcycle Vehicles - Nuraeni Puji Astuti; Ritzkal Ritzkal; Ade Hendri Hendrawan; Bayu Adhi Prakosa; Ritzkal, Ritzkal (Universitas Muhammadiyah Yogyakarta, 2020)
Security system to alert and warn when a vehicle is stolen. This tppl aims to provide information to vehicle owners when a vehicle is in danger by sending coordinate points using SMS (Short Message Service) and can be displayed right with the Google Maps application to make it easy for vehicle owners to track or know the position of the vehicle. Vehicle safety system using SMS (Short message Service) and GPS (Global Positioning System) based on microcontroller and displayed with this smartphone utilizing technology that can make it easier for users to use, namely: (1) neo 6 GPS module, (2) the minimum microcontroller system circuit in Atmega Arduino uno module, (3) SIM GSM 800L module, (4) Smartphones, (5) as well as google maps applications and (6) SMS (short message service) which are already smartphones. Making software (software) this tool uses the C programming language and uses the MIT App Inventor Application.